The Delaney Christmas Carol - Hooper, Kay (Random House, 1992)
This Christmas, celebrate the joys of the season with a trio of exquisitely crafted, richly romantic tales by three of the brightest stars in contemporary fiction. Filled with passion, drama, and a touch of magic, this festive gathering of classic stories--available for the first time in ten years--tells about the lives and loves of one unforgettable family and the enchanted heirloom that links one generation.